Polarizing effect of MoSe2-coated optical waveguides - Berahim, N. (2019)
In this paper, an optical waveguide polarizer based on molybdenum diselenide (MoSe2) coating is proposed and demonstrated. By applying drop-casting method, MoSe2 is coated onto an optical polymer waveguide. The extinction ratio is recorded at wavelength of 980 nm, 1310 nm, 1480 nm and 1550 nm. The highest extinction ratio obtained through this experiment is 14.0 dB, in the 1480 nm wavelength region, with MoSe2 coating thickness and coating length of 24 Âµm and 1.2 mm, respectively. This work demonstrates a polarizing effect of MoSe2 coated SU-8 polymer optical waveguide. Â© 2018 The Authors